2000
DOI: 10.1007/s001340000637
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory depression under long-term sedation with sufentanil, midazolam and clonidine has no clinical significance

Abstract: Patients under continuous sedation with sufentanil exhibit a statistically significant rise in arterial PCO2, however this respiratory depression is only slight and has no clinical significance. Mechanically assisted spontaneous ventilation modes can safely be used under continuous sedation with sufentanil, midazolam or clonidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
1
7
0
3
Order By: Relevance
“…Moreover, its context-sensitive half-life (i.e., the time required to obtain a 50% reduction in the plasma drug concentration after the end of the infusion) is sevenfold lower that of fentanyl with, consequently, a reduced risk of accumulation. 4,12,13 Our data confirm and expand the finding of Prause et al, 6 who retrospectively evaluated the charts of 211 critically ill patients receiving a continuous infusion of sufentanil at different doses (range 0.075-1.22 µg·kg -1 ·hr -1 ) to obtain a modified Ramsay sedation score between 2 and 4 during various partial respiratory support modes (continuous positive airway pressure, synchronized intermittent mandatory ventilation or PSV). These authors observed only a modest increase of PaCO 2 from 39.5 ± 7.3 mmHg (before initiating sedation) to 42.7 ± 6.8 mmHg during the continuous infusion of sufentanil.…”
Section: Figure Effects Of Sufentanil On Respirtory Variablessupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, its context-sensitive half-life (i.e., the time required to obtain a 50% reduction in the plasma drug concentration after the end of the infusion) is sevenfold lower that of fentanyl with, consequently, a reduced risk of accumulation. 4,12,13 Our data confirm and expand the finding of Prause et al, 6 who retrospectively evaluated the charts of 211 critically ill patients receiving a continuous infusion of sufentanil at different doses (range 0.075-1.22 µg·kg -1 ·hr -1 ) to obtain a modified Ramsay sedation score between 2 and 4 during various partial respiratory support modes (continuous positive airway pressure, synchronized intermittent mandatory ventilation or PSV). These authors observed only a modest increase of PaCO 2 from 39.5 ± 7.3 mmHg (before initiating sedation) to 42.7 ± 6.8 mmHg during the continuous infusion of sufentanil.…”
Section: Figure Effects Of Sufentanil On Respirtory Variablessupporting
confidence: 83%
“…Unfortunately few data are available regarding the respiratory effects of analgesia-sedation with sufentanil in patients during partial ventilatory support modes. 6 We conducted a prospective physiologic pilot study aimed at evaluating the effects of the continuous infusion of a single sedative, sufentanil, at 0.2 to 0.3 µg·kg -1 ·hr -1 on central respiratory drive, gas exchanges, respiratory pattern and inspiratory impedance of the respiratory system in a group of 12 patients during pressure support ventilation (PSV). P Pa at ti ie en nt ts s a an nd d m me et th ho od ds s Twelve consecutive patients, endotracheally intubated and mechanically ventilated, were enrolled from August to November 2000 in the 21-bed general ICU located in our University Hospital in Rome.…”
Section: Objectifmentioning
confidence: 99%
“…Wappler and coworkers [22] found that continuous infusion of sufentanil (1 μg/kg per hour was given initially) for analgesia and sedation is suitable for intensive care patients with a short stay in the ICU. Prause and colleagues [10] found that critically ill patients under continuous sedation with sufentanil (median 0.44 μg/kg per hour) exhibit a statistically significant rise in arterial carbon dioxide tension, but this respiratory depression is only slight and has no clinical significance. Mechanically assisted spontaneous ventilation modes can safely be used under continuous sedation with sufentanil.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its short duration of action means that the desired analgesic effect will continue for as long as the infusion is continued, and any undesirable side effects will be short-lived following discontinuation [9]. In addition, mechanically assisted spontaneous ventilation modes can safely be used under continuous sedation with sufentanil [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Sufentanil ist ebenfalls ein synthetischer Rezeptoragonist mit hoher Selektivität für den µ  -Rezeptor. Daraus ergibt sich ein für die Analgosedierung günstiges Wirkspektrum mit einer potenten Analgesie und einer im Vergleich zu anderen Opioiden 7geringeren Atemdepression [77]. Eine pathophysiologisch sinnvolle Spontanatmung ist somit leichter zu realisieren.…”
Section: Analgesieunclassified